Compounds that modulate AMPK activity and hepatic steatosis impact the biosynthesis of microRNAs required to maintain lipid homeostasis in hepatocytes - Latorre, Jèssica (EBioMedicine, 2020)
BACKGROUND: While the impact of metformin in hepatocytes leads to fatty acid (FA) oxidation and decreased lipogenesis, hepatic microRNAs (miRNAs) have been associated with fat overload and impaired metabolism, contributing to the pathogenesis of non-alcoholic fatty liver disease (NAFLD). METHODS: We investigated the expression of hundreds of miRNAs in primary hepatocytes challenged by compounds modulating steatosis, palmitic acid and compound C (as inducers), and metformin (as an inhibitor). Then, additional hepatocyte and rodent models were evaluated, together with transient mimic miRNAs transfection, lipid droplet staining, thin-layer chromatography, quantitative lipidomes, and mitochondrial activity, while human samples outlined the translational significance of this work. FINDINGS: Our results show that treatments triggering fat accumulation and AMPK disruption may compromise the biosynthesis of hepatic miRNAs, while the knockdown of the miRNA-processing enzyme DICER in human hepatocytes exhibited increased lipid deposition. In this context, the ectopic recovery of miR-30b and miR-30c led to significant changes in genes related to FA metabolism, consistent reduction of ceramides, higher mitochondrial activity, and enabled β-oxidation, redirecting FA metabolism from energy storage to expenditure. INTERPRETATION: Current findings unravel the biosynthesis of hepatic miR-30b and miR-30c in tackling inadequate FA accumulation, offering a potential avenue for the treatment of NAFLD. FUNDING: Instituto de Salud Carlos III (ISCIII), Govern de la Generalitat (PERIS2016), Associació Catalana de Diabetis (ACD), Sociedad Española de Diabetes (SED), Fondo Europeo de Desarrollo Regional (FEDER), Xunta de Galicia, Ministerio de Economía y Competitividad (MINECO), “La Caixa” Foundation, and CIBER de la Fisiopatología de la Obesidad y Nutrición (CIBEROBN).